Design A Bird Midge Tool Using Arduino-Based Laser Sensors - Ade Hidayatulloh; Alexius Ulan Bani; Fifto Nugroho (Journal of Mathematics and Technology (MATECH), 2022)
Pests are one of the main enemies for farmers which can reduce the level of production of these types of plants. One of the pests that often disturb rice farmers, among others, are bird pests, which are currently not a bit annoying with the continued increase in bird populations. The purpose of making this tool is to obtain a design of a prototype of a rice-eating bird repellent device based on Arduino Uno, which functions as a substitute for the task of farmers to protect rice plants from attacks by birds that eat rice seeds. This bird repellent uses a laser sensor as a detector and a servo motor as a rope mover. Arduino Uno (AT-Mega 328) microcontroller is used as tool controller and power supply as a power source.